Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
14.7 kB
/-
Copyright (c) 2015 Jeremy Avigad. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Jeremy Avigad, Robert Y. Lewis
-/
import algebra.order.ring
import algebra.group_power.ring
/-!
# Lemmas about the interaction of power operations with order
Note that some lemmas are in `algebra/group_power/lemmas.lean` as they import files which
depend on this file.
-/
variables {A G M R : Type*}
section preorder
variables [monoid M] [preorder M] [covariant_class M M (*) (≀)]
@[to_additive nsmul_le_nsmul_of_le_right, mono]
lemma pow_le_pow_of_le_left' [covariant_class M M (function.swap (*)) (≀)]
{a b : M} (hab : a ≀ b) : βˆ€ i : β„•, a ^ i ≀ b ^ i
| 0 := by simp
| (k+1) := by { rw [pow_succ, pow_succ],
exact mul_le_mul' hab (pow_le_pow_of_le_left' k) }
attribute [mono] nsmul_le_nsmul_of_le_right
@[to_additive nsmul_nonneg]
theorem one_le_pow_of_one_le' {a : M} (H : 1 ≀ a) : βˆ€ n : β„•, 1 ≀ a ^ n
| 0 := by simp
| (k + 1) := by { rw pow_succ, exact one_le_mul H (one_le_pow_of_one_le' k) }
@[to_additive nsmul_nonpos]
lemma pow_le_one' {a : M} (H : a ≀ 1) (n : β„•) : a ^ n ≀ 1 := @one_le_pow_of_one_le' Mα΅’α΅ˆ _ _ _ _ H n
@[to_additive nsmul_le_nsmul]
theorem pow_le_pow' {a : M} {n m : β„•} (ha : 1 ≀ a) (h : n ≀ m) : a ^ n ≀ a ^ m :=
let ⟨k, hk⟩ := nat.le.dest h in
calc a ^ n ≀ a ^ n * a ^ k : le_mul_of_one_le_right' (one_le_pow_of_one_le' ha _)
... = a ^ m : by rw [← hk, pow_add]
@[to_additive nsmul_le_nsmul_of_nonpos]
theorem pow_le_pow_of_le_one' {a : M} {n m : β„•} (ha : a ≀ 1) (h : n ≀ m) : a ^ m ≀ a ^ n :=
@pow_le_pow' Mα΅’α΅ˆ _ _ _ _ _ _ ha h
@[to_additive nsmul_pos]
theorem one_lt_pow' {a : M} (ha : 1 < a) {k : β„•} (hk : k β‰  0) : 1 < a ^ k :=
begin
rcases nat.exists_eq_succ_of_ne_zero hk with ⟨l, rfl⟩,
clear hk,
induction l with l IH,
{ simpa using ha },
{ rw pow_succ,
exact one_lt_mul'' ha IH }
end
@[to_additive nsmul_neg]
lemma pow_lt_one' {a : M} (ha : a < 1) {k : β„•} (hk : k β‰  0) : a ^ k < 1 :=
@one_lt_pow' Mα΅’α΅ˆ _ _ _ _ ha k hk
@[to_additive nsmul_lt_nsmul]
theorem pow_lt_pow' [covariant_class M M (*) (<)] {a : M} {n m : β„•} (ha : 1 < a) (h : n < m) :
a ^ n < a ^ m :=
begin
rcases nat.le.dest h with ⟨k, rfl⟩, clear h,
rw [pow_add, pow_succ', mul_assoc, ← pow_succ],
exact lt_mul_of_one_lt_right' _ (one_lt_pow' ha k.succ_ne_zero)
end
@[to_additive nsmul_strict_mono_right]
lemma pow_strict_mono_left [covariant_class M M (*) (<)] {a : M} (ha : 1 < a) :
strict_mono ((^) a : β„• β†’ M) :=
Ξ» m n, pow_lt_pow' ha
end preorder
section linear_order
variables [monoid M] [linear_order M] [covariant_class M M (*) (≀)]
@[to_additive nsmul_nonneg_iff]
lemma one_le_pow_iff {x : M} {n : β„•} (hn : n β‰  0) : 1 ≀ x ^ n ↔ 1 ≀ x :=
⟨le_imp_le_of_lt_imp_lt $ λ h, pow_lt_one' h hn, λ h, one_le_pow_of_one_le' h n⟩
@[to_additive]
lemma pow_le_one_iff {x : M} {n : β„•} (hn : n β‰  0) : x ^ n ≀ 1 ↔ x ≀ 1 :=
@one_le_pow_iff Mα΅’α΅ˆ _ _ _ _ _ hn
@[to_additive nsmul_pos_iff]
lemma one_lt_pow_iff {x : M} {n : β„•} (hn : n β‰  0) : 1 < x ^ n ↔ 1 < x :=
lt_iff_lt_of_le_iff_le (pow_le_one_iff hn)
@[to_additive]
lemma pow_lt_one_iff {x : M} {n : β„•} (hn : n β‰  0) : x ^ n < 1 ↔ x < 1 :=
lt_iff_lt_of_le_iff_le (one_le_pow_iff hn)
@[to_additive]
lemma pow_eq_one_iff {x : M} {n : β„•} (hn : n β‰  0) : x ^ n = 1 ↔ x = 1 :=
by simp only [le_antisymm_iff, pow_le_one_iff hn, one_le_pow_iff hn]
variables [covariant_class M M (*) (<)] {a : M} {m n : β„•}
@[to_additive nsmul_le_nsmul_iff]
lemma pow_le_pow_iff' (ha : 1 < a) : a ^ m ≀ a ^ n ↔ m ≀ n := (pow_strict_mono_left ha).le_iff_le
@[to_additive nsmul_lt_nsmul_iff]
lemma pow_lt_pow_iff' (ha : 1 < a) : a ^ m < a ^ n ↔ m < n := (pow_strict_mono_left ha).lt_iff_lt
end linear_order
section div_inv_monoid
variables [div_inv_monoid G] [preorder G] [covariant_class G G (*) (≀)]
@[to_additive zsmul_nonneg]
theorem one_le_zpow {x : G} (H : 1 ≀ x) {n : β„€} (hn : 0 ≀ n) :
1 ≀ x ^ n :=
begin
lift n to β„• using hn,
rw zpow_coe_nat,
apply one_le_pow_of_one_le' H,
end
end div_inv_monoid
namespace canonically_ordered_comm_semiring
variables [canonically_ordered_comm_semiring R]
theorem pow_pos {a : R} (H : 0 < a) (n : β„•) : 0 < a ^ n :=
pos_iff_ne_zero.2 $ pow_ne_zero _ H.ne'
end canonically_ordered_comm_semiring
section ordered_semiring
variables [ordered_semiring R] {a x y : R} {n m : β„•}
lemma zero_pow_le_one : βˆ€ n : β„•, (0 : R) ^ n ≀ 1
| 0 := (pow_zero _).le
| (n + 1) := by { rw [zero_pow n.succ_pos], exact zero_le_one }
theorem pow_add_pow_le (hx : 0 ≀ x) (hy : 0 ≀ y) (hn : n β‰  0) : x ^ n + y ^ n ≀ (x + y) ^ n :=
begin
rcases nat.exists_eq_succ_of_ne_zero hn with ⟨k, rfl⟩,
induction k with k ih, { simp only [pow_one] },
let n := k.succ,
have h1 := add_nonneg (mul_nonneg hx (pow_nonneg hy n)) (mul_nonneg hy (pow_nonneg hx n)),
have h2 := add_nonneg hx hy,
calc x^n.succ + y^n.succ
≀ x*x^n + y*y^n + (x*y^n + y*x^n) :
by { rw [pow_succ _ n, pow_succ _ n], exact le_add_of_nonneg_right h1 }
... = (x+y) * (x^n + y^n) :
by rw [add_mul, mul_add, mul_add, add_comm (y*x^n), ← add_assoc,
← add_assoc, add_assoc (x*x^n) (x*y^n), add_comm (x*y^n) (y*y^n), ← add_assoc]
... ≀ (x+y)^n.succ :
by { rw [pow_succ _ n], exact mul_le_mul_of_nonneg_left (ih (nat.succ_ne_zero k)) h2 }
end
theorem pow_lt_pow_of_lt_left (Hxy : x < y) (Hxpos : 0 ≀ x) (Hnpos : 0 < n) :
x ^ n < y ^ n :=
begin
cases lt_or_eq_of_le Hxpos,
{ rw ← tsub_add_cancel_of_le (nat.succ_le_of_lt Hnpos),
induction (n - 1), { simpa only [pow_one] },
rw [pow_add, pow_add, nat.succ_eq_add_one, pow_one, pow_one],
apply mul_lt_mul ih (le_of_lt Hxy) h (le_of_lt (pow_pos (lt_trans h Hxy) _)) },
{ rw [←h, zero_pow Hnpos], apply pow_pos (by rwa ←h at Hxy : 0 < y),}
end
lemma pow_lt_one (hβ‚€ : 0 ≀ a) (h₁ : a < 1) {n : β„•} (hn : n β‰  0) : a ^ n < 1 :=
(one_pow n).subst (pow_lt_pow_of_lt_left h₁ hβ‚€ (nat.pos_of_ne_zero hn))
theorem strict_mono_on_pow (hn : 0 < n) : strict_mono_on (Ξ» x : R, x ^ n) (set.Ici 0) :=
Ξ» x hx y hy h, pow_lt_pow_of_lt_left h hx hn
theorem one_le_pow_of_one_le (H : 1 ≀ a) : βˆ€ (n : β„•), 1 ≀ a ^ n
| 0 := by rw [pow_zero]
| (n+1) := by { rw pow_succ, simpa only [mul_one] using mul_le_mul H (one_le_pow_of_one_le n)
zero_le_one (le_trans zero_le_one H) }
lemma pow_mono (h : 1 ≀ a) : monotone (Ξ» n : β„•, a ^ n) :=
monotone_nat_of_le_succ $ Ξ» n,
by { rw pow_succ, exact le_mul_of_one_le_left (pow_nonneg (zero_le_one.trans h) _) h }
theorem pow_le_pow (ha : 1 ≀ a) (h : n ≀ m) : a ^ n ≀ a ^ m :=
pow_mono ha h
theorem le_self_pow (ha : 1 ≀ a) (h : 1 ≀ m) : a ≀ a ^ m :=
eq.trans_le (pow_one a).symm (pow_le_pow ha h)
lemma strict_mono_pow (h : 1 < a) : strict_mono (Ξ» n : β„•, a ^ n) :=
have 0 < a := zero_le_one.trans_lt h,
strict_mono_nat_of_lt_succ $ Ξ» n, by simpa only [one_mul, pow_succ]
using mul_lt_mul h (le_refl (a ^ n)) (pow_pos this _) this.le
lemma pow_lt_pow (h : 1 < a) (h2 : n < m) : a ^ n < a ^ m :=
strict_mono_pow h h2
lemma pow_lt_pow_iff (h : 1 < a) : a ^ n < a ^ m ↔ n < m :=
(strict_mono_pow h).lt_iff_lt
lemma pow_le_pow_iff (h : 1 < a) : a ^ n ≀ a ^ m ↔ n ≀ m :=
(strict_mono_pow h).le_iff_le
lemma strict_anti_pow (hβ‚€ : 0 < a) (h₁ : a < 1) : strict_anti (Ξ» n : β„•, a ^ n) :=
strict_anti_nat_of_succ_lt $ Ξ» n,
by simpa only [pow_succ, one_mul] using mul_lt_mul h₁ le_rfl (pow_pos hβ‚€ n) zero_le_one
lemma pow_lt_pow_iff_of_lt_one (hβ‚€ : 0 < a) (h₁ : a < 1) : a ^ m < a ^ n ↔ n < m :=
(strict_anti_pow hβ‚€ h₁).lt_iff_lt
lemma pow_lt_pow_of_lt_one (h : 0 < a) (ha : a < 1) {i j : β„•} (hij : i < j) : a ^ j < a ^ i :=
(pow_lt_pow_iff_of_lt_one h ha).2 hij
@[mono] lemma pow_le_pow_of_le_left {a b : R} (ha : 0 ≀ a) (hab : a ≀ b) : βˆ€ i : β„•, a^i ≀ b^i
| 0 := by simp
| (k+1) := by { rw [pow_succ, pow_succ],
exact mul_le_mul hab (pow_le_pow_of_le_left _) (pow_nonneg ha _) (le_trans ha hab) }
lemma one_lt_pow (ha : 1 < a) {n : β„•} (hn : n β‰  0) : 1 < a ^ n :=
pow_zero a β–Έ pow_lt_pow ha (pos_iff_ne_zero.2 hn)
lemma pow_le_one : βˆ€ (n : β„•) (hβ‚€ : 0 ≀ a) (h₁ : a ≀ 1), a ^ n ≀ 1
| 0 hβ‚€ h₁ := (pow_zero a).le
| (n + 1) hβ‚€ h₁ := (pow_succ' a n).le.trans (mul_le_one (pow_le_one n hβ‚€ h₁) hβ‚€ h₁)
lemma sq_pos_of_pos (ha : 0 < a) : 0 < a ^ 2 := by { rw sq, exact mul_pos ha ha }
end ordered_semiring
section ordered_ring
variables [ordered_ring R] {a : R}
lemma sq_pos_of_neg (ha : a < 0) : 0 < a ^ 2 := by { rw sq, exact mul_pos_of_neg_of_neg ha ha }
lemma pow_bit0_pos_of_neg (ha : a < 0) (n : β„•) : 0 < a ^ bit0 n :=
begin
rw pow_bit0',
exact pow_pos (mul_pos_of_neg_of_neg ha ha) _,
end
lemma pow_bit1_neg (ha : a < 0) (n : β„•) : a ^ bit1 n < 0 :=
begin
rw [bit1, pow_succ],
exact mul_neg_of_neg_of_pos ha (pow_bit0_pos_of_neg ha n),
end
end ordered_ring
section linear_ordered_semiring
variables [linear_ordered_semiring R] {a b : R}
lemma pow_le_one_iff_of_nonneg {a : R} (ha : 0 ≀ a) {n : β„•} (hn : n β‰  0) : a ^ n ≀ 1 ↔ a ≀ 1 :=
begin
refine ⟨_, pow_le_one n ha⟩,
rw [←not_lt, ←not_lt],
exact mt (Ξ» h, one_lt_pow h hn),
end
lemma one_le_pow_iff_of_nonneg {a : R} (ha : 0 ≀ a) {n : β„•} (hn : n β‰  0) : 1 ≀ a ^ n ↔ 1 ≀ a :=
begin
refine ⟨_, λ h, one_le_pow_of_one_le h n⟩,
rw [←not_lt, ←not_lt],
exact mt (Ξ» h, pow_lt_one ha h hn),
end
lemma one_lt_pow_iff_of_nonneg {a : R} (ha : 0 ≀ a) {n : β„•} (hn : n β‰  0) : 1 < a ^ n ↔ 1 < a :=
lt_iff_lt_of_le_iff_le (pow_le_one_iff_of_nonneg ha hn)
lemma pow_lt_one_iff_of_nonneg {a : R} (ha : 0 ≀ a) {n : β„•} (hn : n β‰  0) : a ^ n < 1 ↔ a < 1 :=
lt_iff_lt_of_le_iff_le (one_le_pow_iff_of_nonneg ha hn)
lemma sq_le_one_iff {a : R} (ha : 0 ≀ a) : a^2 ≀ 1 ↔ a ≀ 1 :=
pow_le_one_iff_of_nonneg ha (nat.succ_ne_zero _)
lemma sq_lt_one_iff {a : R} (ha : 0 ≀ a) : a^2 < 1 ↔ a < 1 :=
pow_lt_one_iff_of_nonneg ha (nat.succ_ne_zero _)
lemma one_le_sq_iff {a : R} (ha : 0 ≀ a) : 1 ≀ a^2 ↔ 1 ≀ a :=
one_le_pow_iff_of_nonneg ha (nat.succ_ne_zero _)
lemma one_lt_sq_iff {a : R} (ha : 0 ≀ a) : 1 < a^2 ↔ 1 < a :=
one_lt_pow_iff_of_nonneg ha (nat.succ_ne_zero _)
@[simp] theorem pow_left_inj {x y : R} {n : β„•} (Hxpos : 0 ≀ x) (Hypos : 0 ≀ y) (Hnpos : 0 < n) :
x ^ n = y ^ n ↔ x = y :=
(@strict_mono_on_pow R _ _ Hnpos).inj_on.eq_iff Hxpos Hypos
lemma lt_of_pow_lt_pow {a b : R} (n : β„•) (hb : 0 ≀ b) (h : a ^ n < b ^ n) : a < b :=
lt_of_not_ge $ Ξ» hn, not_lt_of_ge (pow_le_pow_of_le_left hb hn _) h
lemma le_of_pow_le_pow {a b : R} (n : β„•) (hb : 0 ≀ b) (hn : 0 < n) (h : a ^ n ≀ b ^ n) : a ≀ b :=
le_of_not_lt $ Ξ» h1, not_le_of_lt (pow_lt_pow_of_lt_left h1 hb hn) h
@[simp] lemma sq_eq_sq {a b : R} (ha : 0 ≀ a) (hb : 0 ≀ b) : a ^ 2 = b ^ 2 ↔ a = b :=
pow_left_inj ha hb dec_trivial
lemma lt_of_mul_self_lt_mul_self (hb : 0 ≀ b) : a * a < b * b β†’ a < b :=
by { simp_rw ←sq, exact lt_of_pow_lt_pow _ hb }
end linear_ordered_semiring
section linear_ordered_ring
variable [linear_ordered_ring R]
lemma pow_abs (a : R) (n : β„•) : |a| ^ n = |a ^ n| :=
((abs_hom.to_monoid_hom : R β†’* R).map_pow a n).symm
lemma abs_neg_one_pow (n : β„•) : |(-1 : R) ^ n| = 1 :=
by rw [←pow_abs, abs_neg, abs_one, one_pow]
theorem pow_bit0_nonneg (a : R) (n : β„•) : 0 ≀ a ^ bit0 n :=
by { rw pow_bit0, exact mul_self_nonneg _ }
theorem sq_nonneg (a : R) : 0 ≀ a ^ 2 :=
pow_bit0_nonneg a 1
alias sq_nonneg ← pow_two_nonneg
theorem pow_bit0_pos {a : R} (h : a β‰  0) (n : β„•) : 0 < a ^ bit0 n :=
(pow_bit0_nonneg a n).lt_of_ne (pow_ne_zero _ h).symm
theorem sq_pos_of_ne_zero (a : R) (h : a β‰  0) : 0 < a ^ 2 :=
pow_bit0_pos h 1
alias sq_pos_of_ne_zero ← pow_two_pos_of_ne_zero
theorem pow_bit0_pos_iff (a : R) {n : β„•} (hn : n β‰  0) : 0 < a ^ bit0 n ↔ a β‰  0 :=
begin
refine ⟨λ h, _, λ h, pow_bit0_pos h n⟩,
rintro rfl,
rw zero_pow (nat.zero_lt_bit0 hn) at h,
exact lt_irrefl _ h,
end
theorem sq_pos_iff (a : R) : 0 < a ^ 2 ↔ a β‰  0 :=
pow_bit0_pos_iff a one_ne_zero
variables {x y : R}
theorem sq_abs (x : R) : |x| ^ 2 = x ^ 2 :=
by simpa only [sq] using abs_mul_abs_self x
theorem abs_sq (x : R) : |x ^ 2| = x ^ 2 :=
by simpa only [sq] using abs_mul_self x
theorem sq_lt_sq : x ^ 2 < y ^ 2 ↔ |x| < |y| :=
by simpa only [sq_abs]
using (@strict_mono_on_pow R _ _ two_pos).lt_iff_lt (abs_nonneg x) (abs_nonneg y)
theorem sq_lt_sq' (h1 : -y < x) (h2 : x < y) : x ^ 2 < y ^ 2 :=
sq_lt_sq.2 (lt_of_lt_of_le (abs_lt.2 ⟨h1, h2⟩) (le_abs_self _))
theorem sq_le_sq : x ^ 2 ≀ y ^ 2 ↔ |x| ≀ |y| :=
by simpa only [sq_abs]
using (@strict_mono_on_pow R _ _ two_pos).le_iff_le (abs_nonneg x) (abs_nonneg y)
theorem sq_le_sq' (h1 : -y ≀ x) (h2 : x ≀ y) : x ^ 2 ≀ y ^ 2 :=
sq_le_sq.2 (le_trans (abs_le.mpr ⟨h1, h2⟩) (le_abs_self _))
theorem abs_lt_of_sq_lt_sq (h : x^2 < y^2) (hy : 0 ≀ y) : |x| < y :=
by rwa [← abs_of_nonneg hy, ← sq_lt_sq]
theorem abs_lt_of_sq_lt_sq' (h : x^2 < y^2) (hy : 0 ≀ y) : -y < x ∧ x < y :=
abs_lt.mp $ abs_lt_of_sq_lt_sq h hy
theorem abs_le_of_sq_le_sq (h : x^2 ≀ y^2) (hy : 0 ≀ y) : |x| ≀ y :=
by rwa [← abs_of_nonneg hy, ← sq_le_sq]
theorem abs_le_of_sq_le_sq' (h : x^2 ≀ y^2) (hy : 0 ≀ y) : -y ≀ x ∧ x ≀ y :=
abs_le.mp $ abs_le_of_sq_le_sq h hy
lemma sq_eq_sq_iff_abs_eq_abs (x y : R) : x^2 = y^2 ↔ |x| = |y| :=
by simp only [le_antisymm_iff, sq_le_sq]
@[simp] lemma sq_le_one_iff_abs_le_one (x : R) : x^2 ≀ 1 ↔ |x| ≀ 1 :=
by simpa only [one_pow, abs_one] using @sq_le_sq _ _ x 1
@[simp] lemma sq_lt_one_iff_abs_lt_one (x : R) : x^2 < 1 ↔ |x| < 1 :=
by simpa only [one_pow, abs_one] using @sq_lt_sq _ _ x 1
@[simp] lemma one_le_sq_iff_one_le_abs (x : R) : 1 ≀ x^2 ↔ 1 ≀ |x| :=
by simpa only [one_pow, abs_one] using @sq_le_sq _ _ 1 x
@[simp] lemma one_lt_sq_iff_one_lt_abs (x : R) : 1 < x^2 ↔ 1 < |x| :=
by simpa only [one_pow, abs_one] using @sq_lt_sq _ _ 1 x
lemma pow_four_le_pow_two_of_pow_two_le {x y : R} (h : x^2 ≀ y) : x^4 ≀ y^2 :=
(pow_mul x 2 2).symm β–Έ pow_le_pow_of_le_left (sq_nonneg x) h 2
end linear_ordered_ring
section linear_ordered_comm_ring
variables [linear_ordered_comm_ring R]
/-- Arithmetic mean-geometric mean (AM-GM) inequality for linearly ordered commutative rings. -/
lemma two_mul_le_add_sq (a b : R) : 2 * a * b ≀ a ^ 2 + b ^ 2 :=
sub_nonneg.mp ((sub_add_eq_add_sub _ _ _).subst ((sub_sq a b).subst (sq_nonneg _)))
alias two_mul_le_add_sq ← two_mul_le_add_pow_two
end linear_ordered_comm_ring